Contribution to the examinationof mother-tongue use of Hungarians in Croatia (Eastern-Slavonia) - Kovács, Lea (Array, 2010)
The paper presents the results of a field-research which aims to detect the use of the mother tongue among the Hungarian minority living scattered in Eastern Slavonia (Croatia). On the basis of a poll-mesure that included more than hundred people speaking Hungarian as a minority language on the field the authors depict in detail how the place, the partner and the topic of the communication influences the choice of the language to be used in certain situations. The results show that the use of Hungarian as a minority language is more and more reduced to the age group above sixty years. Besides that, regarding the place, the partners and the topic, the role of the Hungarian language also decreases in the formal, official situations in connection with the everyday topics.